Variation of aflatoxin levels in stored edible seed and oil samples and risk assessment in the local population - Iqbal, Shahzad Zafar; Waqas, Muhammad; Razis, Ahmad Faizal Abdull; Usman, Sanusi; Ali, Nada Basheir; Asi, Muhammad Rafique (MDPI AG, 2022)
Five hundred and twenty samples of edible seeds and oilseeds (sunflower, palm, peanut, sesame, cotton, and grapeseed) were purchased from markets, farmers, and superstores in the central cities of Punjab, Pakistan. A total of 125 (48.1%) edible seed samples from a 6 ≤ months storage period, and 127 (48.8%) from a 2 ≥ years storage period were found to be infested with AFs. The average elevated amount of AFB1 and total AFs was observed in a 2 ≥ years storage period, i.e., 28.6 ± 4.5 and 51.3 ± 10.4 μg/kg, respectively, in sesame seeds. The minimum amount of AFB1 and total AFs was observed in palm seed samples with a storage period of 6 ≤ months, i.e., 9.96 ± 2.4, and 11.7 ± 1.90 μg/kg, respectively. The maximum amount of AFB1 and total AFs were observed in peanut oil samples, i.e., 21.43 ± 2.60 and 25.96 ± 4.30 μg/kg, respectively, with a storage period of 2 ≥ years. Therefore, the maximum dietary intake of 59.60 ng/kg/day was observed in oil samples stored at a ≥ 2 years storage period. The results of the present study concluded that a significant difference was found in the amounts of total AFs in edible seed samples stored at 6 ≤ months and 2 ≥ years storage periods (p < 0.05).